SISTEM INFORMASI PENDAFTARAN MUSABAQAHTILAWATIL QURAN (MTQ) KABUPATEN SUMBAWA BERBASIS WEB - Yuniar Andriani; Eri Sasmita Susanto,; M. Julkarnain (Program Studi Informatika Universitas Teknologi Sumbawa, 2020)
Musabaqah Tilawatil Qur’an (MTQ) is a large religious activity that is routinely carried out annually, one of which is in Sumbawa Regency. This study aims to build an information system based on WEB, namely, Application of Musabaqah Tilawatil Qur’an Registration (MTQ) in Sumbawa Regency. This application is built using the PHP programming language model using MySql as its database. Software development method uses Extreme Programming (XP) Software testing is done through black-box testing. Data collection techniques in research using observation, interviews, documentation and literature study. The end of this research is the application of registration of Musabaqah Tilawatil Qur'an (MTQ) of Sumbawa Regency based on WEB, which is useful to help the processing of registration data of the Muslim Brotherhood in Tilawatil Qur'an (MTQ) of Sumbawa Regency